Carles Porta and Tor: The Intersection between Investigative Journalism, Sensationalism, and Capitalization of a Crime - Fitó-Carreras, Maria; Freire-Sánchez, Alfonso; Vidal-Mestre, Monserrat (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This research focuses on the work of journalist Carles Porta, in particular on the incident of a real crime in Tor, a small village in the Catalan Pyrenees. Porta has conducted nearly three decades of journalistic investigation, culminating in the production of Tor, la muntanya maleïda (“Tor, The Cursed Mountain”), a true crime documentary series. The aim of this study is to explore how an investigative journalist adopts the role of a storyteller and transforms a real event into a sensa : The existence is observed of a distinctive authorial mark characterized by his interventions, interactions and emotional involvement with the characters throughout the narrative